Bibliometric analysis of the interplay between epilepsy and microglia: trends, hotspots, and emerging research areas - Zhang, Shouye; Yang, Xiaotong; Wang, Yuping (Frontiers in Neurology, 2024)
Background Epilepsy, a common neurological disorder, has been increasingly associated with neuroinflammation, especially microglia activation. To gain insights into the research trends and patterns in this intersection, we conducted a bibliometric analysis of studies published between 2005 and 2024. Using the Web of Science Core Collection, we identified 1,229 relevant articles and reviews, focusing on the relationship between epilepsy and microglia. Methods We employed the Bibliometrix R package and VOSviewer to analyze the data. Our search strategy combined epilepsy-related terms with microglia and microglial cell keywords. The analysis encompassed publication trends, country and institutional contributions, journal sources, authors, keywords, and thematic evolution. Results The number of publications has steadily increased, particularly after 2019, indicating growing research interest. The United States, China, and Germany emerged as the most productive countries, with extensive collaboration between China and the United States. Epilepsia and Journal of Neuroinflammation were the most influential journals. Aronica E, Vezzani A, and Engel T were the most prolific authors. Thematic analysis revealed clusters focused on temporal lobe epilepsy, epilepsy-related disorders, and microglia activation. Over the past several years, research has shifted from fundamental brain function studies to in-vivo investigations of specific molecular mechanisms. The CSTB (−) mouse model and NF-κB signaling pathway both merit further in-depth investigation. Conclusion In conclusion, this bibliometric study reveals a surge in epilepsy-microglia research, led by key countries, journals, and researchers. Temporal lobe epilepsy, epilepsy-related disorders, and microglia activation are focal themes. Future directions include exploring microglia activation mechanisms, utilizing animal models, and interdisciplinary approaches.